Explicating the Premodern: An Introductory Political Philosophy of Strauss, Arendt and MacIntyre - Reyaz, Aiman; Ata, Shakil Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
There are always historians of philosophy and political science who remind us that past thinkers may well have resources that most contemporary philosophers and political scientists in a rush to create or respond to the latest theory, sometimes ignore. In the second half of the 20th century, a number of such thinkers came to believe that the anti-realism, relativism and end of critical thinking that some contemporaries were announcing were actually the result of a wrong road having been taken in the 18th century. The question is, the problems of relativism and postmodernism or the problems that postmodernism points to, do they indicate that modernity or the enlightenment was already a wrong term.